Kepuasan dan Kepercayaan Pelanggan sebagai Faktor Penentu Loyalitas pada Layanan Transportasi Online Grab di Kota Medan - Lenti Susanna Saragih; Aurora Elise Putriku; Yuliana Simbolon; Sasti Permata; Sri Handayani (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine the role of customer satisfaction and trust as determinants of loyalty in Grab online transportation services in Medan City. The research method used is a qualitative approach with a survey method. Data collection was carried out through the distribution of online questionnaires to 60 respondents selected using purposive sampling technique. The data were analyzed descriptively using a Likert scale. The results showed that customer satisfaction, which includes service quality, driving experience, driver professionalism, vehicle cleanliness, and complaint handling, was rated quite well by the respondents. Customer trust in Grab as a safe, transparent, and reliable transportation choice has also proven to be an important factor in building loyalty. However, customer loyalty to Grab is not very strong, given the intense competition in the online transportation industry. The implication is that Grab and similar companies need to continue improving service quality, ensuring customer safety and comfort, responding to complaints effectively, and implementing effective marketing strategies to retain customers. This research provides valuable insights for online transportation service providers in their efforts to enhance customer satisfaction, trust, and loyalty amidst dynamic market competition.